An Examination of Factors Associated With Student Resiliency. Issue 3 (19th May 2022) - Hand, Mikel W.; Evans, Jennifer; Swenty, Constance; White, Ann; Chen, Chen
Abstract : Background: Student resiliency, success, and retention are top priorities for nursing programs. Purpose: The purpose of the cross-sectional descriptive study was to identify factors associated with the resiliency level and physical and mental health of nursing students. Methods: A cross-sectional descriptive study design was used with a convenience sample of 199 nursing students from organizations that comprise the Community Patient Safety Coalition Nursing Research Consortium. Resiliency was measured with the Connor Davidson Resiliency Scale. Physical and mental health was measured with the Patient Reported Outcomes Measurement Information System Global Health Short Form. Results: Most of the nursing students in the sample were female (92%), White (94%), and in BSN programs (74.4%). Students had low resiliency ( P < .0001) and low physical and mental health ( P < .0001) compared with the general population. Conclusions: Student resilience was positively correlated to self-perception of physical and mental health.